Ascaris lumbricoides coinfection reduces tissue damage by decreasing IL-6 levels without altering clinical evolution of pulmonary tuberculosis or Th1/Th2/Th17 cytokine profile - Santos,João Hugo Abdalla (2019)
Abstract INTRODUCTION: Immunological control of Mycobacterium tuberculosis infection is dependent on the cellular immune response, mediated predominantly by Th1 type CD4+ T cells. Polarization of the immune response to Th2 can inhibit the host immune protection against pathogens. Patients with tuberculosis coinfected with helminths demonstrate more severe pulmonary symptoms, a deficiency in the immune response against tuberculosis, and an impaired response to anti-tuberculosis therapy. METHODS: We evaluated the cellular immune response and the impact of the presence of Ascaris lumbricoides on the immune and clinical response in pulmonary tuberculosis patients. Ninety-one individuals were included in the study: 38 tuberculosis patients, 11 tuberculosis patients coinfected with Ascaris lumbricoides and other helminths, 10 Ascaris lumbricoides patients, and 34 non-infected control individuals. Clinical evolution of pulmonary tuberculosis was studied on 0, 30, 60, and 90 days post-diagnosis of Mycobacterium tuberculosis and Ascaris lumbricoides. Furthermore, immune cells and plasma cytokine profiles were examined in mono/coinfection by Mycobacterium tuberculosis and Ascaris lumbricoides using flow cytometry. RESULTS: There were no statistical differences in any of the evaluated parameters and the results indicated that Ascaris lumbricoides infection does not lead to significant clinical repercussions in the presentation and evolution of pulmonary tuberculosis. CONCLUSIONS: The association with Ascaris lumbricoides did not influence the Th1, Th2, and Th17 type responses, or the proportions of T lymphocyte subpopulations. However, higher serum levels of IL-6 in tuberculosis patients may explain the pulmonary parenchymal damage.